YOU LOOK LIKE A LITTLE GIRL! shouted my teacher of the 4th year of elementary education. sexual and gender dissident bodies in school and art classes (Revista Apotheke, 2022)
The objective of the article is to present theoretical-methodological notes of Education and of Dissident Art Education to tension and confront the educational and social system of modernity/coloniality. It problematizes the School as a public education system and its “authoritarian” pedagogy of “fear” and “compulsory masculinity” to legitimize “heteroreason” as a single truth. It exercises educational curation as a proposition for the enjoyment and reading of images in the teaching, learning and creation processes in visual arts, articulating and intersecting artistic practices of sexual and gender dissidences with issues of race, class, sexuality, gender, ethnicity and coloniality. Defends the emergence of Education and Art Education Dissidents antiethnocidal, antiracist, antitranslgbtphobic, antipatriarchal, anticapitalist, anticapacitalist, antisexist, transfeminist, decolonial.
Keywords: Education Dissident; Art Education Dissident; Artistic Practices; Sexual and Gender Dissidences; Educational Curatorship